Economic shifts and financial strain: Karnataka farmers’ journey in the first two decades of the 21st century - Singh, Ajad; Atri, Jyoti (Journal of Social Review and Development, 2024)
This study examines the economic transformations and financial pressures faced by farmers in Karnataka from 2002-03 to 2018-19. It explores shifts in landholding patterns, credit accessibility, income trends, and indebtedness among different farmer categories. Utilizing data from the Situation Assessment Survey (SAS) conducted in 2003 and 2019, the analysis reveals a trend towards smaller landholdings and increased credit access, especially among marginal and small farmers. Significant income growth is observed, particularly in agricultural earnings, alongside rising consumption expenditures. However, the debt burden has substantially increased, with variations across farmer categories. The findings highlight the importance of supporting sustainable land management, enhancing financial inclusion, and promoting diversified income sources to ensure the long-term economic stability of farmers in Karnataka.